Volume 2B: Advanced Manufacturing 2013
DOI: 10.1115/imece2013-63160
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Scaling Effects in Meso-Micro EDM

Abstract: The ability to remove chip volumes in micro-nano scale has enabled implementation of electrical discharge machining (EDM) in high precision and micro-machining of difficult to machine electrically conductive materials, such as metals and ceramics. Despite of its wide spread application in tool making and precision applications, the limited process understanding limits exploitation of the EDM process capabilities. In current work, scaling effects caused due to the electrode projection area and erosion depth hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It is important to emphasize that the research here developed concerns the analysis of single electric discharges, whereas the material removal in the DEDM process occurs by several subsequent discharges. Different pause durations between electric discharges may lead to different plasma properties in DEDM, such as already reported by Maradia [22] for EDM in hydrocarbon oil. Thus, effects of multiple electric discharges and their resulting micro plasmas are not considered in the scope of the present work and need further investigation.…”
Section: It Is Not Yet Known If This Phenomenon Also Occurs In Dedmmentioning
confidence: 70%
“…It is important to emphasize that the research here developed concerns the analysis of single electric discharges, whereas the material removal in the DEDM process occurs by several subsequent discharges. Different pause durations between electric discharges may lead to different plasma properties in DEDM, such as already reported by Maradia [22] for EDM in hydrocarbon oil. Thus, effects of multiple electric discharges and their resulting micro plasmas are not considered in the scope of the present work and need further investigation.…”
Section: It Is Not Yet Known If This Phenomenon Also Occurs In Dedmmentioning
confidence: 70%
“…15. It is seen that the highest material removal rate is achieved for the pulse duration of 20 s for micro-scale graphite electrodes due to the scaling effects, as investigated by [35]. Aluminium with the lowest melting temperature has the highest material removal rate, whereas TiAl6V4 with the highest melting temperature of the analysed materials has the lowest material removal rate.…”
Section: Process Parameter Analysismentioning
confidence: 79%
“…6. Here, definition of the macro-, meso-and micro-scale is based on the observed scaling effects in EDM process, where the pulse durations required to achieve highest material removal rates are dependent on the electrode surface area, as shown in [35]. Using 20 A, mode M2 and 1000 s pause duration, 9 mm deep cavities are eroded in steel 1.2343.…”
Section: Process Parameter Analysismentioning
confidence: 99%
“…For longer pulse durations, the metal vapour density increases in these discharges surrounded by a large gas bubble. This hypothesis has been validated by [2], where light emission spectroscopy of discharge plasma is performed during multiple discharge process in near-real erosion conditions. It is found that the portion of metallic vapour increases in the discharge plasma and the mean discharge voltage decreases when the electrode projection area becomes smaller.…”
Section: Underlying Mechanismmentioning
confidence: 80%
“…However, it is a wellknown fact that volumetric wear at sharp edges, corners and needle-like microstructures is much more pronounced than for larger electrode surface areas [1]. Also, process parameters required to achieve low electrode wear and high material removal rate are dependent on the electrode projection area due to the scaling effects, as shown by [2]. Thus, applying suitable parameters depending on the geometric spark location is necessary but difficult since the distribution of discharges on electrodes is stochastic [3].…”
Section: Introductionmentioning
confidence: 99%